Design of an Android-Based Fiqh Learning Application - Nofri Yudi Arifin (Engineering and Technology International Journal, 2025)
The development of information and communication technology (ICT) has opened up new opportunities to enhance the quality of education, including Islamic religious education. This study aims to design and develop an interactive Android-based application for Fiqh learning that aligns with the curriculum and is easily accessible to students. The research employs a Research and Development (R&D) method using a prototyping model, involving both teachers and students throughout the development stages. The results show that the application received positive feedback in terms of usability, engaging interface, and relevance of the content. The implementation in an Islamic-based school environment indicated that the application successfully increased students' interest and motivation in learning while assisting teachers in delivering Fiqh material more effectively. These findings suggest that mobile applications can serve as innovative learning tools for Fiqh in the digital era.